The analysis of Sandra Cisneros' House on Mango Street based on social criticism of Gloria Anzaldúa's Borderlands: La Frontera - Grum, Špela (Acta neophilologica, 2015)
The article deals with the main female characters that appear in Sandra Cisneros' collection of vignettes, House on Mango Street (1991). It sheds light on their lives and motives for their actions, through social criticism of Gloria Anzaldúa and the main points she establishes in her semi-autobiographical collection of essays Borderlands: La Frontera (1999). The topics Anzaldúa addresses give an insight into the Chicano identity, and the struggle of Chicano women in particular. Through her vantage point, I discuss gender roles, the immigrants' search for identity and their quest for a more dignified life, by trying to reconcile the antagonizing forces of the different parts of their identity.
Keywords: "La Frontera"; "The house on Mango Street"; 1991; 1999; American literature; ameriška književnost; Anzaldúa, Gloria, 1942-2004; borderlands; Chicano; Cisneros, Sandra, 1954-; gender roles; immigrants; Literarne študije; Mestiza; migranti; vloge spolov